THE EFFECT OF BEETROOT JUICE (Beta vulgaris L.) ON THE CONCENTRATION OF SPERMATOZOA IN WISTAR RATS EXPOSED TO MOSQUITO COIL SMOKE - Dean Pandu Eko Sapto; Donna Hermawati; RR. Mahayu Dewi Ariani; Farmaditya Eka Putra (JURNAL KEDOKTERAN DIPONEGORO (DIPONEGORO MEDICAL JOURNAL), 2021)
Background: Mosquito coil smoke contains Allethrin that can increase the free radical effect. This process  may result in the damage of the cell membranes that triggered by oxidative stress. Oxidative stress can affect spermatogenesis and decreasing the quality of spermatozoa, including the spermatozoa concentration. Beetroot contain flavonoid as an antioxidant which can counteract the free radicals in the body.Purpose: To identify the effect of beetroot juice in the spermatozoa concentration of Wistar rats that exposed by mosquito coil smoke.Method: This study used Post Test Only control group design. The samples were 28 male Wistar rats that divided into 4 groups. The Control Group(-) was a group without treatment. The Control Group(+) was only exposed by mosquito coil smoke. Group P1 was exposed by mosquito coil smoke and given 8 ml of beetroot juice. P2 group was exposed by mosquito coil smoke and given 16 ml of beetroot juice. For 56 days, on the 57th day all rats were terminated and spermatozoa concentrations were examined.Results: The average concentration of spermatozoa was: Group K(-)=20,00; Group K(+)=8,00; P1 group=12,40; P2 group=17,20. One Way ANOVA test found there were significant differences among the five treatment groups. Post-Hoc test found there were significant differences among K(-) with K(+), K(-) with P1, K(-) with P2, K(+) with P1, K(+) with P2 and P1 with P2.Conclusion: Beetroot juice administration increasing the spermatozoa concentration of male wistar rats that exposed by cigarette smoke.Keywords: Mosquito coil smoke, beetroot juice, spermatozoa concentration